Stress distribution analysis of seat and non-seat preparation design for orden cast post using 2D finite element method - Miranda, Aldilla; Subrata, Gantini; Hasratiningsih, Zulia; Dirgantara, Tatacipta (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2011)
The post is used to retain a core that supports the definitive restoration. One of the important factors in the prognosis of post-endodontic restoration system is the post space preparation design which effects to the distribution of stresses. The purpose of this study was to analyze the effect of post space preparation design at the cervical area of the root to the stress distribution on static loading using (two dimensions) finite element method. This was a numeric simulation study using two 2D digital models: seat and non-seat design of maxillary central incisors using commercial software of finite element. The procedures of pre-processing, solution, and post-processing were used to evaluate the distribution of internal stress caused by static loading 110 N which was applied at 135Â° angle with tooth longitudinal axis on the palatal surface of the core. Both models of restoration with cast post-core of Orden alloy were divided into 15,400 triangular elements. This study showed that the stress distribution from the loading location to the location of stress concentration and the value of maximum stress at cervical part of the root at non-seat design was lower than the seat design (seat design 3.69 times greater than non-seat). This study proved that non-seat design distributes stress better than seat design.